The Impact of Multimedia on Motivating Learning Enthusiasm in Class X Akidah Akhlak Subjects at State Aliyah Madrasah - Rafli, Muh.; Mawardi, Mawardi; Tahrim , Tasdin (Educational Journal of Learning Technology, 2024)
This study evaluated the use of multimedia in MAN Palopo, focusing on Akidah Akhlak class XA Tahfiz. Using Classroom Action Research for two months, this study involved 36 students. Cycle I with lectures, Cycle II fix with multimedia PowerPoint. The findings of Cycle I recorded shortcomings, while Cycle II brought significant positive impacts, including improved learning, student comfort, and learning activities. Simple statistical formulas analyze quantitative data, while qualitative data are obtained from interviews and observations. The recommendation is to continue using multimedia to maintain a positive impact. This research contributes to the enrichment of learning and the improvement of teaching quality at MAN Palopo.